La ricerca sulla follia dei giuristi romani. Una storia poco conosciuta - De Simone, Gianfranco (Il sogno della farfalla, 2005)
This study into the sources of the ancient Roman jurists aims at reconstructing their research into the notion of folly which had been carried out over a long period, dating from the Law of the XII tables (450 b.C.) to the Justinian code (A.D.). Juridical source have always been inexplicably ignored by historians of medicine and psychiatry. The author documents the fact that jurists in the Roman world took a novel approach in linking the concept of folly, the person and the law, and allowed for an original reflection on mental disease as a context where the recognition of folly was not linked to a medical diagnosis, it was the magistrate who was called to intervene in ascertaining and “treating” cases of madness. In considering the “furiosus” a mental case, jurists went clearly beyond the medical notions of the day whereby madness (“mania”) was viewed as illness of the body by priests, philosophers and other experts of the irrational who dealt with notion of madness.